ORGANIC FARMING AND COMPOST TECHNOLOGY - S.N. Pandey; S.N. Pandey (New Delhi alfa, 2014)
This book provides role of organic fertilizer, manures and composts in organic farming.
Organic farming Compost Technology Organic Fertilizers
Keywords: Organic farming